Ifosfamide-Induced Encephalopathy in Relapsed Lymphoma: Report of Two Cases - Takaryanto, Davin; Harti, Gusti Fungani; Oehadian, Amaylia (Faculty of Medicine Universitas Padjadjaran, 2024)
Objective: Ifosfamide is a chemotherapeutic drug available for various malignancy, including lymphoma. Ifosfamide has adverse effects including myelosuppression, nephrotoxicity, hemorrhagic cystitis, and neurotoxicity. Encephalopathy is a severe manifestation of neurotoxicity due to ifosfamide, with an incidence of 10–40%. This study aimed to report two cases of ifosfamide-induced encephalopathy.Case: This case studies reported two relapsed lymphoma patients with almost similar characteristics who received ifosfamide chemotherapy. The first case of 48-year-old woman with relapsed High-Grade B-cell lymphoma stage IIIBE while the second case of 38-year-old woman with relapsed non-hodgkin lymphoma. The first case showed a good outcome with improvement in consciousness 48 hours after stopping ifosfamide and thiamine, while the second case experienced tumor lysis syndrome, leading to the death of the patient.Conclusion: Mechanism of ifosfamide-induced encephalopathy remains unclear, with the hypothesis from the neurotoxic effects of the resultant metabolite chloracetyldehide. Radiology examination of the brain and electroencephalography is required to rule out other differential diagnoses. Early recognition of adverse effects, followed by immediate discontinuation of ifosfamide, administration of therapy, such as methylene blue and/or thiamine, and supportive treatment usually produced good outcomes.